2019
DOI: 10.1177/1363461519854831
|View full text |Cite
|
Sign up to set email alerts
|

Using a person-generated mental health outcome measure in large clinical trials in Kenya and Pakistan: Self-perceived problem responses in diverse communities

Abstract: Health care should be informed by the physical, socioeconomic, mental, and emotional well-being of the person, and account for social circumstances and culture. Patient-generated outcome measures can contribute positively to mental health research in culturally diverse populations. In this study, we analysed qualitative responses to the Psychological Outcome Profiles (PSYCHLOPS) Questionnaire—a patient-generated outcome measure based on open-ended questions, and compared the qualitative responses gathered to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…Overall, the results show the prevalence of psychological problems and the importance of social network and local displacement-related factors on psychological wellbeing, and illustrate psychological problems as the common consequence of a range of stressors. Psychological 27 [44] 15 [33] 23 [40] 65 [40] Interpersonal 15 [25] 14 [30] 15 [26] 44 [27] Physical/psychosomatic health 13 [21] 13 [28] 10 [18] 36 [22] Separation from family members 11 [18] 8 [17] 13 [23] 32 [20] Related to war/home country 7 [11] 6 [14] 7 [12] 20 [12] Related to family duties 10 [16] 5 [13] 2 [4] 17 [10] Personal development/unmet personal needs 0 [0] 3 [7] 7 [12] 10 [6] Note: N J number of participants in Jordan, N T number of participants in Turkey, N S number of participants in Switzerland, n/a not applicable Finances 11 [18] 17 [37] 6 [11] 34 [21] Camp related issues 26 [43] n/a n/a 26 [16] Government regulations 3 [5] 4 [9] 12 [21] 19 [12] Housing 2 [3] 5 [11] 11 [19] 18 [11] Medical treatment 6 [10] 6 [13] 3…”
Section: Psychological Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the results show the prevalence of psychological problems and the importance of social network and local displacement-related factors on psychological wellbeing, and illustrate psychological problems as the common consequence of a range of stressors. Psychological 27 [44] 15 [33] 23 [40] 65 [40] Interpersonal 15 [25] 14 [30] 15 [26] 44 [27] Physical/psychosomatic health 13 [21] 13 [28] 10 [18] 36 [22] Separation from family members 11 [18] 8 [17] 13 [23] 32 [20] Related to war/home country 7 [11] 6 [14] 7 [12] 20 [12] Related to family duties 10 [16] 5 [13] 2 [4] 17 [10] Personal development/unmet personal needs 0 [0] 3 [7] 7 [12] 10 [6] Note: N J number of participants in Jordan, N T number of participants in Turkey, N S number of participants in Switzerland, n/a not applicable Finances 11 [18] 17 [37] 6 [11] 34 [21] Camp related issues 26 [43] n/a n/a 26 [16] Government regulations 3 [5] 4 [9] 12 [21] 19 [12] Housing 2 [3] 5 [11] 11 [19] 18 [11] Medical treatment 6 [10] 6 [13] 3…”
Section: Psychological Problemsmentioning
confidence: 99%
“…Stressors and mental health of SRAs have been predominantly assessed through nomothetic measurements -often developed and validated in western contexts [20]. Studies have shown that standard instruments often fail to encompass all aspects of distress in cross-cultural settings, and that it is a fallacy to assume that symptoms in different cultural contexts carry the same significance across cultures [21][22][23]. Client-generated outcome measurements are person-centred by definition and unlike standardized measures, they seek to encompass the individuals' phenomenological experiences as well as their priorities, local values, perspectives and expectations [22,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…This was a low number in comparison with previous studies, where more than 90% of patients' responses to PSYCHLOPS allowed total score calculation (Ashworth et al 2004(Ashworth et al , 2005(Ashworth et al , 2009. In other studies, PSYCHLOPS has been administered as an interview measure, to ensure no missing data in populations with literacy issues (Harper Shehadeh et al 2019).…”
Section: Discussionmentioning
confidence: 88%
“…Table 2 Overview Categories of self-reported problems of the three study populations. [44] 15 [33] 23 [40] 65 [40] Interpersonal 15 [25] 14 [30] 15 [26] 44 [27] Physical/psychosomatic health 13 [21] 13 [28] 10 [18] 36 [22] Separation from family members 11 [18] 8 [17] 13 [23] 32 [20] Related to war/home country 7 [11] 6 [14] 7 [12] 20 [12] Related to family duties…”
Section: Overview Reported Problemsmentioning
confidence: 99%
“…Stressors and mental health of SRAs have been predominantly assessed through nomothetic measurements -often developed and validated in western contexts (Kirmayer & Pedersen, 2014). Studies have shown that standard instruments often fail to encompass all aspects of distress in cross-cultural settings, and that it is a fallacy to assume that symptoms in different cultural contexts carry the same signi cance across cultures (Hassan, Ventevogel, Jefee-Bahloul, Barkil-Oteo, & Kirmayer, 2016;Shehadeh et al, 2019;Wells, Wells, & Lawsin, 2015). Client-generated outcome measurements are person-centred by de nition and unlike standardized measures, they seek to encompass the individuals' phenomenological experiences as well as their priorities, local values, perspectives and expectations (Ashworth et al, 2007;Hassan et al, 2016;Sales, Neves, Alves, & Ashworth, 2018).…”
Section: Introductionmentioning
confidence: 99%